2021
DOI: 10.3390/su13073771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Lockdown on Physical Activity and Health-Related Quality of Life in Older Adults Who Regularly Exercise

Abstract: The aim of the study was to analyze the effect of social distancing on physical activity (PA) and Health-Related Quality of Life (HRQoL) in active Spanish older adults according to their physical functionality. The study included 58 older adults aged 76.24 ± 6.00 years who were enrolled in a supervised physical exercise program before the COVID-19 outbreak. Anthropometric, physical function, physical activity and HRQoL were measured at baseline (October 2019). After the two-month lockdown due to the COVID-19, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 36 publications
0
24
1
4
Order By: Relevance
“…In addition, the traditional exercise and training environment is not always adapted to the physical condition of the seniors and can lead to injuries and other harm [ 27 ]. The current COVID-19 pandemic restrains the possibility of outside or collective physical exercise, leading to even greater sedentarization of older adults [ 28 , 29 , 30 ]. Remote supervised physical exercise training thus could become an optimal solution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the traditional exercise and training environment is not always adapted to the physical condition of the seniors and can lead to injuries and other harm [ 27 ]. The current COVID-19 pandemic restrains the possibility of outside or collective physical exercise, leading to even greater sedentarization of older adults [ 28 , 29 , 30 ]. Remote supervised physical exercise training thus could become an optimal solution.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos incluídos mostram que a prática de exercício física protocolados é benéfica saúde mental de idosos no contexto da pandemia a de COVID-19, foi verificado através dos mesmos, melhora do estresse percebido, sintomas de depressão, estimulação cognitiva, prosperidade sociopsicológica e qualidade de vida mental (Aldy et al, 2021;Casanova et al, 2020;Esain et al, 2021;Granacher et al, 2020;Liu et al, 2020;Mansfield et al, 2021;Murukesu et al 2020;Qi et al, 2021;Solianik et al, 2021).…”
Section: Resultsunclassified
“…Todos os estudos tiveram intervenção com algum tipo de exercício físico, em Casanova et al, (2020) A maioria da amostra foi de idosos saudáveis, que não foi informado patologia ou a patologia não fazia parte de interesse do estudo (Esain et al, 2021;Granacher et al, 2020;Mansfield et al, 2021;Qi et al, 2021;Solianik et al, 2021) Três estudos investigaram o uso da teles saúde, em que apresentam potencial para benefícios da suade mental em idosos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Previous studies have reported significant decrease in physical activity (8,14). Visser et al underlined that negative impact of the COVID-19 pandemic on PA may increase the risk of frailty, sarcopenia and disability (15).…”
Section: Introductionmentioning
confidence: 99%